Dissociations in the neural substrates of language and social functioning in autism spectrum disorder. Issue 8 (26th October 2018) - Crutcher, Jason; Martin, Alex; Wallace, Gregory L.
Abstract : Impairments in social communication (coupled with intact nonsocial language skills) are common in autism spectrum disorder (ASD). However, the neural correlates of these social communication deficits in adolescents and young adults with ASD are not fully understood. The communication checklist self‐report (CC‐SR) was administered to adolescents and young adults with ASD ( n = 52) and typically developing (TD) controls ( n = 64) to assess structural‐language, pragmatic‐language, and social‐engagement. One high‐resolution T1‐weighted structural image was obtained from each participant. FreeSurfer was used to quantify cortical thickness. A main effect of diagnosis, with the ASD group performing worse than the TD group on all three CC‐SR scales, and a diagnosis by scale interaction, driven by low social‐engagement self‐ratings in the ASD group, were found. There were also group differences in the relationship between scores on two of the three CC‐SR scales and cortical thickness in multiple regions (pragmatic‐language: left rostral frontal; social‐engagement: left medial prefrontal). These interactions were driven by poorer self‐ratings of language/social skills associated with decreased cortical thickness in the ASD group, while in the TD group worse self‐ratings were associated with thicker cortex. Self‐ratings of language/social‐communication were lower in the ASD than the TD group. Moreover, language/social‐communication self‐ratings showed a different relationship with cortical thickness for the ASD and TD groups in the left inferior frontal region for pragmatic language ratings and the left medial prefrontal cortex for social engagement ratings. These findings suggest thinner cortex is associated with more impaired pragmatic language and social communication abilities in ASD. Autism Res 2018, 11: 1175–1186 . © 2018 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The present study examines the associations between brain structure and language/social communication ability in adolescents and young adults with autism spectrum disorder (ASD) as compared to neurotypical adolescents and young adults. We utilized thickness of the cerebral cortex as a measure of brain structure, and we found different correlations between language or social communication ability and cortical thickness in distinct regions for the ASD and TD groups. These findings suggest that for regions implicated in language/social communication ability, decreased cortical thickness is associated with more impaired pragmatic language and social communication abilities in ASD.